FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN JAM TANGAN ALEXANDRE CHRISTIE DI KOTA BATAM - Kurniawati, Kurniawati; Evyanto, Winda (SCIENTIA JOURNAL, 2021)
Along with the development of the times and technology, Alexandre Christie watches are a luxury brand because they are original watches and have good quality. The technique used in this study was a pseudo sample that used the population of people in nagoya area, the sample used as many as 150 respondents. The measuring instrument used is 5 points using the Likert scale. Data analysis method used is multiple linear regression analysis, data quality test in this study using validity test and reliability test, classical assumption test in this study using normality test, multicolinearity test and heteroskedastiity test and multiplier test using multiple linear regression analysis and determination coefficient analysis (R2), while hypothesis test in this study using t test and F test with the help of spss 21 statistic software. Based on the results of this study shows that consumer behavior, lifestyle and trust have a positive and significant effect on purchasing decisions from t count > t tables and significant values <0.05 as well as consumer behavior, lifestyle and trust together have a positive and significant influence on purchasing decisions from f calculate > f table and significant value < 0.05.